Pengaruh Penyuluhan tentang Menarche terhadap Pengetahuan dan Sikap Remaja Putri Pra Menstruasi - Maria Ulfa; Ika Agustina (Journal of Ners and Midwifery, 2014)
Adolescence is a stage in human life which is often referred to as puberty. And of the various characteristics of puberty, menarche is a fundamental difference between pubertal male and female puberty. Method: The research design was pre eksperimental design. With the approach of one group pretest-posttest design. The sample are 100 student of SMPN 1 Blitar City, it was choosen using simple random sampling technique. The data was collected by questionnaire. Result : Based on statistical tests Wilcoxon sign rank test obtained sig = 0.000. This shows 0.000 <0.05 that the presence of the above found that the pvalue (0,000) <0.05, it can be concluded that there are significant health promotion on the attitudes of young women. Discussion : Young women more active to increase the knowledge by obtaining information about reproductive health care, especially about mensruation.